Analisis Perilaku Keuangan dan Literasi Keuangan Terhadap Tekanan Financial Bagi Mahasiswa dengan Kemampuan Ekonomi Keluarga sebagai Variabel Moderasi - Putriasari, Dea; Fachruzzaman, Fachruzzaman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to examine the relationship between financial behavior and financial literacy on financial stress experienced by college students, with family economic capacity acting as a moderator variable. Using a quantitative approach, data were collected through structured questionnaires distributed to college students from various economic backgrounds. This study used multiple regression analysis to assess the direct and moderator effects between these variables. The results of the study indicate that financial behavior and financial literacy significantly affect college students' financial stress. College students with higher financial literacy tend to manage their financial stress more effectively. In addition, the moderator role of family economic capacity shows that college students from families with higher economic stability experience less financial stress, even when financial behavior and literacy levels are less than optimal. This study contributes to understanding the dynamics of financial stress in college students, emphasizing the importance of improving financial literacy and considering family economic factors to reduce financial stress. These insights provide valuable implications for educational institutions and policy makers to design targeted financial education programs and support systems for college students.